PENGARUH CASH TURNOVER, RECEIVABLE TURNOVER DAN INVENTORY TURNOVER TERHADAP PROFITABILITAS PADA PERUSAHAAN SUBSEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Syahamah, Aisyah; Susilowati, Dwi; Hernadi Moorcy, Nadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
This research aims to provide a partial impact of Cash Turnover, Receivables Turnover, and Inventory Turnover on profitability. Profitability is measured using Return on Assets (ROA) which reflects the effectiveness of asset management in generating company profits. The data used in this research was obtained from internal and external sources that can be accessed online, including publication information. The focus of the research is on the financial reports of pharmaceutical companies listed on the Indonesia Stock Exchange for the 2019–2023 period. The analytical method used is multiple linear regression, with an emphasis on partial tests to show the influence of each independent variable on the dependent variable. The results of the analysis show that Cash Turnover does not have a positive and insignificant influence on Return on Assets (ROA), Receivable Turnover does not have a negative and insignificant influence on ROA, and Inventory Turnover does not have a positive and insignificant influence on ROA.